Zwyczaje zakupowe Polaków w latach 1995-2006 - Idzik, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article presents decision making process of the consumers relating to FMCG (including food) purchases. The research showed that changes in Polish economy and globalization trends have an influence on consumer's preferences and behaviours. Among others the growing time value for consumers, factors affecting shop choice and consumer's favourite means of promotion were shown. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 281-287